2022
DOI: 10.1186/s40814-022-01113-0
|View full text |Cite
|
Sign up to set email alerts
|

App-based intervention among adolescents with persistent pain: a pilot feasibility randomized controlled trial

Abstract: Background Persistent pain in adolescence adversely affects everyday life and is an important public health problem. The primary aim was to determine the feasibility of an 8-week app-based self-management intervention to reduce pain and improve health-related quality of life in a community-based population of adolescents with persistent pain. A secondary aim was to explore differences in health outcomes between the intervention and control groups. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…In total, 63% of apps provided psychoeducational content, with 77% of these apps also providing specific exercises based on the presented psychoeducation. Almost half of the apps aimed to support adolescents in specific behavior changes, with three apps focusing on setting goals ( 51 , 61 , 65 ) and three apps focusing on problem-solving strategies ( 59 , 64 , 74 ). Another frequently used feature was a toolbox with useful skills for difficult situations ( n = 9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 63% of apps provided psychoeducational content, with 77% of these apps also providing specific exercises based on the presented psychoeducation. Almost half of the apps aimed to support adolescents in specific behavior changes, with three apps focusing on setting goals ( 51 , 61 , 65 ) and three apps focusing on problem-solving strategies ( 59 , 64 , 74 ). Another frequently used feature was a toolbox with useful skills for difficult situations ( n = 9).…”
Section: Resultsmentioning
confidence: 99%
“…Four out of these nine apps provided a safety plan for suicidal or self-harm crisis management ( 66 , 69 , 78 , 80 ). Furthermore, three apps provided a diary feature for app users ( 59 , 61 , 78 ) and four apps had a community forum that enabled app users to communicate with other affected adolescents ( 49 , 54 , 65 , 75 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mobile phone apps might be particularly useful for digital native adolescents. However, some studies have found low levels of engagement for pediatric pain self-management apps, suggesting that further research is needed to understand how adoption can be enhanced [ 13 , 14 ]. In an adult cohort, allowing people with chronic pain to be able to tell their own story through a comprehensive assessment has been identified as a key component in enhancing the experience of pain education [ 11 ].…”
Section: Introductionmentioning
confidence: 99%